Instrumental or intrinsic? Human rights alignment in intergovernmental organizations - David Benjamin Weyrauch; Christoph Valentin Steinert (The Review of International Organizations, 2021)
Why do states' human rights records converge with co-members in intergovernmental organizations (IGOs)? This study provides new insights on whether interactions in IGOs have the capacity to genuinely transform state preferences or whether norm diffusion is a consequence of instrumental processes. We leverage information about the timing of human rights alignment to disentangle intrinsic from instrumental motives. We hypothesize that instrumental motives find expression in pre-membership alignment and reversions to original normative standards after IGO exits. Intrinsic motives lead to gradual alignment during IGO membership and result in stable normative changes beyond IGO exits. Using varying-slopes, varying intercepts models, we investigate the distance on human rights indices between individual states and IGO means. While we find evidence for systematic convergence during IGO membership, no significant changes occur before and after IGO membership. Testing alignment of different physical integrity rights, we find no evidence for instrumental shifts to clandestine repression during IGO membership. Overall, the results suggest that norm alignment in IGOs is at least not exclusively instrumentally motivated. Our findings support constructivist arguments on state interests and suggest that IGOs are capable of transforming states' human rights related preferences.
Keywords: 320; Intergovernmental organizations; Human rights; Norm diffusion; Socialization; Strategic repression